(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2019)
An indirect translation is a translation in language C which is produced not from the source text in language A but based on a mediating text in language B which itself is a translation of the source text. One issue arising from indirect translation is the issue of fidelity, that is, the extent to which the translation reflects the original source text due to the presence of the mediating text. The aim of this paper is to examine this issue by focusing on a translation in Malay entitled Nurani Tanah Melayu, the English mediating text, The Soul of Malaya and the French source text, Malaisie. More specifically, the paper aims to determine the types of relationship that exist between the three texts and to establish the changes made by the translator in the process of translating. Ultimately, the aim is to establish whether the process of indirect translation produces a translated text that deviates from the original text and if so, whether the mediating text plays a role in the deviations that occur. For this purpose, a comparison is carried out between the three texts with the aim of establishing the similarities and differences between them. The findings indicate that the deviations from the French source text in the Malay translation are not necessarily due to the mediating text. Additionally, in cases where the Malay translation reflects the French source text, the adherence to the French text is not necessarily due to the assistance the mediating text.